Med Aromat Plants 2019
DOI: 10.35248/2167-0412.19.8.339
|View full text |Cite
|
Sign up to set email alerts
|

Hepato-Protective Effect from Natural Compounds, Biological Products and Medicinal Plant Extracts on Antitubercular Drug-Induced Liver Injuries: A Systematic Review

Abstract: Tuberculosis is mainly treated with rifampicin, pyrazinamide, isoniazide, ethambutol and/or streptomycin; however, the first three cause hepato-and nephro-toxicity, then the patient abandons therapy. This cause contributes to the failure of the treatment and favors the appearance of drug-resistant strains. Currently, alternatives are being sought to counteract this hepatic-damage, and medicinal plants, natural compounds and/or biological products are of great interest. In this manuscript we describe current da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It should be noted that of these three drugs, PZA is the most hepatotoxic. [31][32][33] At present, natural substances or extracts from medicinal plants with nephro-and/or hepatoprotective effect are wanted. In this regard, SIL was use as positive control because show a hepatoprotector effect in vivo and in vitro against the hepatic damage caused by antiTB drugs, in addition to having an antitubercular and antimycobacterial effect.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that of these three drugs, PZA is the most hepatotoxic. [31][32][33] At present, natural substances or extracts from medicinal plants with nephro-and/or hepatoprotective effect are wanted. In this regard, SIL was use as positive control because show a hepatoprotector effect in vivo and in vitro against the hepatic damage caused by antiTB drugs, in addition to having an antitubercular and antimycobacterial effect.…”
Section: Discussionmentioning
confidence: 99%
“…The reported pharmacological activities of Euphorbia fusiformis are antioxidant, antifungal, diuretic, antiinflammatory, antibacterial, hepatoprotective, antinociceptive, and galactagogue. It has been observed that it increases intestinal transit time; also, the plant is being evaluated for its use in reversing female infertility 2,3,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
mentioning
confidence: 99%